Sturm-Liouville problem in multiplicative fractional calculus - Gulsen, Tuba; Goktas, Sertac; Abdeljawad, Thabet; Gurefe, Yusuf (Amer Inst Mathematical Sciences-Aims, 2024)
Multiplicative calculus, or geometric calculus, is an alternative to classical calculus that relies on division and multiplication as opposed to addition and subtraction, which are the basic operations of classical calculus. It offers ff ers a geometric interpretation that is especially helpful for simulating systems that degrade or expand exponentially. Multiplicative calculus may be extended to fractional orders, much as classical calculus, which enables the analysis of systems having fractional scaling properties. So, in this paper, the well-known Sturm-Liouville problem in fractional calculus is reformulated in multiplicative fractional calculus. The considered problem consists of the SturmLiouville operator using multiplicative conformable derivatives on the equation and on boundary conditions. This research aimed to explore some of the problem's spectral aspects, like being selfadjointness of the operator, orthogonality of different ff erent eigenfunctions, and reality of all eigenvalues. In this specific situation, Green's function is also recreated.
Keywords: geometric calculus; multiplicative conformable fractional calculus; non-Newtonian Calculus; Sturm-Liouville equation